2011
DOI: 10.1111/j.1423-0410.2011.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pathogen reduction technology (Mirasol) on platelet quality when treated in additive solution with low plasma carryover

Abstract: Despite the observed differences in platelet metabolism and activation observed following PRT treatment in PAS and low plasma carryover, the results suggest that treatment and storage of platelets in PAS is no more detrimental to platelets than treatment and storage in plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
90
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(108 citation statements)
references
References 34 publications
14
90
4
Order By: Relevance
“…Treatment with the UVC system appears to accelerate the metabolic rate of platelets, which is similar to the effects of other PI methods [9,10,11]. However, in vivo investigations using the UVC system are showing positive results [5,12].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Treatment with the UVC system appears to accelerate the metabolic rate of platelets, which is similar to the effects of other PI methods [9,10,11]. However, in vivo investigations using the UVC system are showing positive results [5,12].…”
Section: Introductionmentioning
confidence: 78%
“…There appears to be some contradictory evidence regarding the effect of UVC treatment on HSR, with some studies finding a reduction [5,8] and others not [4,6,17]. Similarly, the HSR has been shown to be negatively affected by PI treatment with other systems [10,11]. This effect is of particular interest given that the HSR is one of the few in vitro parameters thought to be associated with post-transfusion efficacy [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS may also play a role in the generation of platelet microparticles and subsequent procoagulant effects [37] as well as in regulating tyrosine phosphorylation of many key proteins involved in platelet signal transduction, including vasodilator-stimulated phosphoprotein (VASP) [34,38]. Similarly, increased metabolism, a reduced ability to aggregate in response to agonists, and increased expression of platelet signaling proteins, including VASP, have been observed in Mirasol- treated platelets [5,9,39,40]. The similarities between the effects of ROS and PI on platelet function are striking.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have concluded that Mirasol treatment exacerbates the effects of the platelet storage lesion, resulting in increased glucose consumption, lactate production, and increased markers of platelet activation [2,3,4,5,6]. Further, we and others have previously demonstrated that Mirasol treatment affects platelet signal transduction and apoptotic protein expression [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%